The Influence of Work Motivation and Job Satisfaction on the Performance of Employees of Perumda Air Minum Wair Pu'an, Sikka Regency - Hendriksia Cindy Prilyastiti; Antonius Philippus Kurniawan; Vinsensius Ama Muda (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
The background of this employee's performance of Perumda Wair Pu'an Water Supply Sikka Regency has not been maximized. This research aims to (1) determine the description of employee performance, work motivation, and job satisfaction; (2) analyze the influence of work motivation and job statistics on employee performance both partially and simultaneously. The population in this research were employees of Perumda Wair Pu'an Water Supply Sikka Regency, totaling 50 people. This research was carried out through a census or saturated sampling due to limited population. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing was done through the F-test and t-test. The descriptive analysis results showed that the variables of employee. Performance, work motivation, and job satisfaction were categorized as good enough. The statistical results of the F test showed that simultaneously the variables Work Motivation and Job Satisfaction had a significant influence on employee performance. The results of the t-test statistic showed that partially the variables of work motivation and job satisfaction had a significant influence on employee performance. The results of the Determination analysis showed that the two independent variables in this research can explain the fluctuation of employee performance by 30.5%.